Infarction of Percheron artery: A rare case report - Ateş, Fatih; Kara, Turgay; Şara, Halil İbrahim and Çoban, Muhammed Sami and Durmaz, Mehmet Sedat and Durmaz, Funda Gökgöz (Journal of Surgery and Medicine, 2019)
The thalamus has strategic cores, which are divided into different functional classes and manage important cortical functions in harmony with each other. The mechanism proposed in the bilateral paramedian thalamic infarction is an occlusion of a single undifferentiated thalamo-perforating artery which is an anatomic variant. This artery, called the Percheron artery, appears from the first segment of the posterior cerebral artery and gives bilateral medial thalamic perforating branches. Bilateral paramedian thalamic infarction causes specific clinical signs and symptoms such as changes in consciousness ranging from letarj to coma, vertical gaze paralysis, ocular congestion loss and amnesia. In this case we aimed to present clinical and radiological features of a rare condition with infarction of percheron artery.